1995
DOI: 10.1136/bmj.310.6985.967
|View full text |Cite
|
Sign up to set email alerts
|

Increasing incidence of tuberculosis in England and Wales: a study of the likely causes

Abstract: Objectisve-To examine factors responsible for the recent increase in tuberculosis in England and Wales.Design-Study of the incidence of tuberculosis (a) Conclusions-The national rise in tuberculosis affects only the poorest areas. Within one such area all residents (white and established ethnic minorities) were affected to a similar extent. The evidence indicates a major role for socioeconomic factors in the increase in tuberculosis and only a minor role for recent immigration from endemic areas. Introducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
65
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(70 citation statements)
references
References 4 publications
(5 reference statements)
4
65
1
Order By: Relevance
“…Thus, the distribution of tuberculosis in this country can more accurately be explained by both measures of ethnicity and deprivation than by either factor alone. This is in contrast to a previous study which concluded that deprivation alone was responsible for the national rise in tuberculosis [7].…”
contrasting
confidence: 56%
See 1 more Smart Citation
“…Thus, the distribution of tuberculosis in this country can more accurately be explained by both measures of ethnicity and deprivation than by either factor alone. This is in contrast to a previous study which concluded that deprivation alone was responsible for the national rise in tuberculosis [7].…”
contrasting
confidence: 56%
“…Several recent studies have found that socioeconomic factors, such as overcrowding and unemployment, are associated with tuberculosis rates in England and Wales [6,7], while other reports from Western Europe [5,8], New Zealand [9] and Canada [10] have documented that immigration from nations where tuberculosis is common has been largely responsible for slowing the decrease in morbidity rates in these developed countries. These studies have shown that the incidence of tuberculosis in immigrant communities is far greater than in the indigenous population.…”
mentioning
confidence: 99%
“…The resurgence of tuberculosis (TB) in recent years in many industrialized countries [1][2][3][4][5][6][7] has shown that the disease occurs frequently in specific groups, such as foreign-born persons from countries with a high prevalence, intravenous drug users and socially marginalized people. In some of these groups there is an additional risk for human immunodeficiency virus (HIV) infection or anti-TB drug resistance [8].…”
mentioning
confidence: 99%
“…Within the developed world, the recent increase has principally been associated with immigration from developing countries [5][6][7], increasing poverty [8][9][10], unemployment [10], overcrowding [11], smoking [12], homelessness [13,14], an ageing indigenous population [15,16] and, particularly within the USA, HIV infection [17,18]. However, other studies, by analysing several geographical measures together, have shown that rates of disease across urban areas of England were geographically more closely associated with the proportion of the population that were of non-White ethnic origin than with economic deprivation indices [19].…”
mentioning
confidence: 99%